Comparison of Polish and Portuguese Economy with a historical perspective - Pietrzak, Marta (2022)
When making an economic comparison of Portugal and Poland, it is worth paying attention to the historical background, demographics, the way of exercising power and the fact that Portugal is in the euro area and Poland remains with its currency. Maybe we will find some similarities, we will notice differences.